Fire-driven fine-scale diversity of Cerrado flowering plants and their bee pollinators in space and time - Ballarin, Caio Simões [UNESP]; Fidelis, Alessandra [UNESP]; Maruyama, Pietro Kiyoshi; Amorim, Felipe Wanderley [UNESP] (Oxford University Press, 2026)
Background and Aims Understanding how floral diversity is structured at fine spatiotemporal scales and how pollinators respond to such dynamics is constrained by scarce high-resolution spatiotemporal data, particularly in highly biodiverse fire-prone tropical ecosystems. We aimed to investigate fine-scale spatial and temporal variation in flowering plant and bee assemblages in the Cerrado and to assess how fire influences different aspects of floral diversity and bee responses. Methods We conducted high-resolution sampling of 1-m2 subplots monitored weekly across two flowering seasons encompassing a fire event in the Cerrado. At this fine scale, we tested whether species turnover of bee-pollinated plants and bee assemblages was stronger across space or time. Using a before– after control–impact design, we evaluated how fire affected the taxonomic, functional and phylogenetic structure of bee-pollinated plant assemblages, as well as bee occurrence, diversity and visitation rates. Key Results We found high fine-scale diversity with many unique flowering plant species combinations across space and time, reflecting the strong turnover typical of the Cerrado. Spatial distance predicted neither flower nor bee assemblage turnover, indicating that plant assemblages are structured by local post-fire conditions rather than dispersal limitation, with bees visiting flower patches haphazardly. In contrast, temporal turnover increased for both flowers and bees with broader temporal windows, reflecting phenological shifts during the flowering season. Fire restructured the fine-scale floral assemblages by increasing the occurrence of bee-pollinated plants while reducing local taxonomic richness and floral abundance, but maintaining functional and phylogenetic diversity, with cascading effects on bee occurrence, diversity and visitation rates. Conclusions Fire induced non-parallel effects across floral diversity dimensions, reshaping resource display and influencing pollinator dynamics. By revealing substantial variation in diversity at fine spatiotemporal scales, our results highlight the limitations of site-level or cross-sectional (snapshot) studies and underscore the ecological value of fine-scale heterogeneity in the Cerrado, as human-driven disturbances and management operate at these scales.
Diversidade em escala fina de flores do Cerrado e de suas abelhas polinizadoras, moldada pelo fogo no espaço e no tempo
Keywords: Bee pollination; Community assembly; Fire events; Functional traits; Phenology; Phylogenetic diversity; Species turnover